Co-Pyrolysis of Waste Polystyrene Foam and Microalgae at Low Temperatures - Ebru Gizem Ormanci; Gamze Ozcakir; Ali Karaduman (Engineering Proceedings)
Fossil fuel reserves have depleted. Therefore, renewable and sustainable energy forms an important issue. Microalgae as a third-generation biomass can be an alternative carbon-neutral fuel source. However, its fuel quality is low. Co-pyrolysis is an important technique to upgrade the fuel quality of microalgae. In this study, we aimed to carry out the pyrolysis of polystyrene and Spirulina sp. microalgae at low temperatures (350, 400, and 450 °C). The experiments were conducted using a semi-batch reactor setup. Co-pyrolytic product yields were calculated. The composition of liquid products was enlightened by using GC-MS. As a result of the analysis, aromatic compounds like styrene and toluene were detected in the co-pyrolytic liquid. Moreover, it was observed that co-pyrolysis increased the solid residue yield while it decreased the liquid and gas product yield.